Concept of barakah in Qur’ān and Sunnah: towards its realization in modern discourse - Demirel, Serdar; Babu Sahib, Hikmatullah (Fatih Sultan Mehmet Vakıf Üniversitesi, 2015)
One of the concepts Islam considers important for human prosperity is the concept of barakah (Divine blessing). It is the increase in quality and quantity of God’s blessing via unseen ways to human life. The word barakah also means to make the felicity constant and permanent, which also means abundance and the continuity of that. However, with modernity barakah has become an alienated concept in the life of modern man. This research explores and discusses the reasons behind the lack of divine blessing in human life in modern times and the profane worldview behind it by highlighting its importance and application through both Qur’ānic and Sunnah texts.